Label Syariah dan Kearifan Lokal sebagai Determinan Keputusan Konsumen Menginap di Hotel Syariah Jember - Kamila Nasywa Aulia Hafizhah; Desi Ratna Ningrum; Nadia Azalia Putri (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study examines the influence of sharia label and local wisdom on consumers’ decisions to stay at sharia hotels in Jember Regency. The growing development of halal tourism has encouraged the hospitality industry to not only comply with Islamic principles but also adapt to local socio-cultural contexts, particularly in non-metropolitan areas. This research adopts a quantitative causal-associative approach using a survey method. Primary data were collected from consumers who had stayed at sharia hotels in Jember, and the data were analyzed using multiple linear regression analysis. The findings indicate that the sharia label and local wisdom simultaneously play an important role in shaping consumers’ stay decisions. The sharia label functions as a signal of trust that strengthens consumers’ positive attitudes and social acceptance toward sharia hotels, while local wisdom enhances emotional comfort and contextual relevance through culturally aligned services and experiences. These results suggest that consumers’ stay decisions are formed through the interaction of religious values and cultural considerations, rather than purely functional evaluations. This study contributes to the literature on halal tourism by integrating sharia compliance and local cultural values within the Theory of Planned Behavior framework and provides practical insights for sharia hotel managers.